PENGARUH STRATEGI PEMASARAN DAN MEDIA SOSIAL TERHADAP PERILAKU KONSUMEN CAFE MALAM - Muhammad Riza Fahlevi; Bachrudin Ali Achmad; Emy Rahmawati (JURNAL BISNIS DAN PEMBANGUNAN, 2021)
A good and right relationship marketing strategy and social media will lead to good consumer behavior as well. This study aims to examine the effect of marketing strategy (X1) and social media (Instagram) (X2) on consumer behavior (Y) café Malam Banjarmasin. This research is a descriptive study, with a sample of 100 at café Malam Banjarmasin consumers. The data collection used a questionnaire, while the data analysis used multiple linear regression. The variables studied were Likert scale. The questionnaire was tested by validity and reliability tests. Data processing using SPSS version 25.0.The t test results on consumer behavior are valid because r > 0.3 and the reliability test shows reliable because alpha cronbach > 0.6. The normality test is obtained 0.05 and it is said that the data is normally distributed and on the normal line of the plot, you can see that the points from the graph spread around the diagonal line and follow the diagonal line. The more the marketing strategy variable (X1) increases, the consumer behavior (Y) increases, while the marketing strategy variable (X1) decreases, the consumer behavior decreases(Y). The conclusion of this study is that there is a marketing strategy and social media that affect consumer behavior by 57%.Keywords: Marketing strategy, social media, consumer behavior.